Effect of Cooking and Preservation Time on Fish Balls Quality Produced from Pangasius Hypophthalmus Meat By product - Ngoc Duc Vu; Thanh Truc Tran; Van Muoi Nguyen (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2023)
The demand for Tra fish (Pangasius hypophthalmus) fillets is increasing every year which also increases the number of fish meat byproducts. Approximately 10% of P. hypophthalmus meat is discarded after the production of fish fillets. This study aimed to develop fish balls from the fishmeat byproduct of P. hypophthalmus fillet then investigated the effect of cooking methods and preservation time on the alteration of its texture, brightness, and total bacterial count (TBC). The raw material, minced byproduct and fish balls were analyzed for pH, protein, fat, and moisture contents. The protein content in Tra fish reached 7.35% and increased to 37.14% after the completion of the processing stages for the finished product. Blanching for 4 minutes at 90°C and steaming for 4 minutes at 100°C resulted in good texture and brightness of fish balls. However, a more effective reduction in total bacterial count was observed during the blanching process. Fish balls were preserved by freezing at -40 °C for 42 days and still maintained stable brightness. However, TBC increased significantly after 7 days, and conversely for the texture of fish balls. A finding on the stability of texture and TBC of fish balls when continued preservation from 7 to 42 days. The utilization and use of by-products from the fish fillet processing industry contribute to improving the economic value of the aquaculture industry.